PENINGKATAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI GERAK PARABOLA DI KELAS X SMAN 12 PEKANBARU - Rossa, Defila; Zulhelmi, Zulhelmi; Syaflita, Dina (JURNAL SPEKTRA, 2023)
Students' high thinking ability is an aspect that needs to be trained by educators. In fact, students' higher-order thinking skills are still relatively low because the learning model applied in schools does not train students' higher-order thinking skills because they are still focused on the teacher. Therefore, researchers conducted research by applying a student-focused learning model, namely the guided inquiry learning model. This study aims to determine the increase and differences in higher order thinking skills between classes that apply the guided inquiry learning model and classes that apply conventional learning. This type of research uses a quasi-experimental non-equivalent posttest control group design. The data collection instrument was a post-test with 13 multiple choice questions. Data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis showed that the high-order thinking skills of X MIPA 5 students were better than X MIPA 6. This was reflected in Class X MIPA 5. The average score of students' higher-order thinking skills was 60.26 and that of the control class was 49.15. The results of the inferential analysis show that the significance value of the independent sample t-test is 0.0004, which means it is less than 0.05. Therefore, from the results of the two analyzes it can be concluded that there is a significant difference in the results of the high-order thinking ability test for students in class X MIPA 5 and class X MIPA 6 and X MIPA 5 getting better results after learning by applying the guided inquiry learning model to parabolic motion material.